Analysis and study of risk factors related to the progression of non-alcoholic fatty liver disease: A retrospective cohort study - JunRan Yang; Zhenhua Zhou (PLoS ONE, 2025)
Objective Non-alcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent worldwide. This study aimed to analyze the risk factors associated with NAFLD progression by collecting and evaluating clinical data of NAFLD patients, providing a scientific basis for its prevention and treatment. Methods Clinical data of NAFLD patients from June 2015 to June 2016 were retrospectively collected, including gender, age, alanine aminotransferase (ALT), aspartate aminotransferase(AST), alkaline phosphatase(ALP),γ-glutamyltranspeptidase (GGT), triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), fasting blood glucose (FBG), and visceral fat area (VFA). All patients were stratified by gender and age, and logistic regression analysis was used to explore the risk factors for NAFLD disease progression. Results ALT, TG, FBG, and VFA were identified as independent risk factors for NAFLD progression. Stratified analysis showed that in male patients, ALT, TG, and VFA were independent risk factors, whereas in female patients, TG, FBG, and VFA were identified as independent risk factors. Age-stratified analysis revealed that ALT, TG, and VFA were significant risk factors for progression in young and middle-aged patients. At the same time, age, ALT, TG, and FBG were substantial in elderly patients. Conclusion Different risk factors should be closely monitored in sex- and age-specific populations to prevent NAFLD progression effectively.